MEASURING THE IMPACT OF INTEREST RATES ON INVESTMENT SPENDING, INFLATION, AND UNEMPLOYMENT IN IRAQ FOR THE PERIOD (2000-2020) - . BADAN, ZAHID. (The Gulf Economist, 2024)
The interest rate is considered one of the effective monetary policy tools that has a major role in influencing the economic activity, especially macroeconomic variables. the researcher used econometric analysis to determine the effect of the interest rate and predict the nature of the relationship to the future through joint integration, relying on a set of tests, including stability tests, and then he relied on the cointegration test to determine the long-term balance between the variables. However, the study found that the cointegration between the variables used is existed, and then he relied on simple regression analysis to show the effect of the interest rate on iraqi economic activity through gross domestic product, inflation, and unemployment during the study period. Furthermore, the study has set a number of conclusions and recommendations, the most important of which is the existence of a long-term balance between the interest rate, gross domestic product, inflation, and unemployment, which means that the interest rate is capable of correcting structural deviations and imbalances in the iraqi economy during the long term. The researcher concluded the ineffectiveness of the interest rate in the Iraqi economy during the short term because the economy suffers from structural problems.